La figura di Luigi Luciano Bonaparte nella linguistica ottocentesca - Lupinu, Giovanni (Verbum – Analecta Neolatina, 2006)
Prince Louis Lucien Bonaparte (1813–1891) was an important pioneer in the field of Basque, English, Italian and Sardinian dialectology, who deserves a much better treatment than what he has received in modern books of history of linguistics. The main aim of this research is to give more accurate information on this subject.